2022
DOI: 10.3389/fnhum.2022.1010076
|View full text |Cite
|
Sign up to set email alerts
|

The mean diffusivity of forceps minor is useful to distinguish amnestic mild cognitive impairment from mild cognitive impairment caused by cerebral small vessel disease

Abstract: ObjectivesIn recent years, the desire to make a more fine-grained identification on mild cognitive impairment (MCI) has become apparent, the etiological diagnosis of MCI in particular. Nevertheless, new methods for the etiological diagnosis of MCI are currently insufficient. The objective of this study was to establish discriminative measures for amnestic mild cognitive impairment (a-MCI) and MCI caused by cerebral small vessel disease (CSVD).Materials and methodsIn total, 20 normal controls (NCs), 33 a-MCI pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Also, for the differentiation between the left and right hemispheres of the human brain, the white matter structures connecting the two hemispheres are very important for the transmission of information and integration of brain functions. It has been reported that the forceps minor may serve as an indicator to differentiate between amnestic mild cognitive impairment (MCI) and MCI caused by cerebral small vessel disease [34].…”
Section: Discussionmentioning
confidence: 99%
“…Also, for the differentiation between the left and right hemispheres of the human brain, the white matter structures connecting the two hemispheres are very important for the transmission of information and integration of brain functions. It has been reported that the forceps minor may serve as an indicator to differentiate between amnestic mild cognitive impairment (MCI) and MCI caused by cerebral small vessel disease [34].…”
Section: Discussionmentioning
confidence: 99%